Evaluation of Regional Rural e-Commerce Development Potential with Intuitive Fuzzy Information Theory - Tao Yang (Advances in Multimedia)
In recent years, China’s Internet industry has developed rapidly, and the Internet has penetrated into all aspects of people’s daily lives. As an emerging transaction model, rural e-commerce is an important channel for precise poverty alleviation. To be specific, rural e-commerce can greatly change the lives of rural people in one way or other ways, thus allowing rural consumers to purchase high-quality and inexpensive goods without having to leave home. In other words, the introduction of national e-commerce into rural areas has changed the lifestyle of rural residents, providing them with great convenience in their daily lives. According to statistics, the level of rural e-commerce development in coastal areas is much higher than that in the mainland, while inland areas are hesitant to develop. Rural areas are a crucial component of Chinese society, and the rural economy is also the main driving force of China’s agricultural economy. In an environment where e-commerce is gradually penetrating various fields, the development of rural e-commerce in China has become more urgent with the new and growing rural demand. To be specific, the development of rural e-commerce has become a hot topic in recent years, and it is necessary to gather efforts from all sides to explore and innovate, so as to promote the healthy and orderly growth of rural e-commerce in China. As one of the effective ways to solve the problems of agricultural industry development and farmers’ affluence, rural e-commerce has played an increasingly obvious role in industrial development, poverty alleviation, employment, and solving the problems of selling agricultural products. At the same time, the proportion of national online sales of agricultural products is also increasing year by year. Many rural areas have abundant natural resources, rich history and culture, and a pleasant ecological environment. As a result, a great number of rural areas are well suited for e-commerce development in terms of the overall environment and physical resources. In recent years, the development of rural e-commerce in China has been very rapid, but it has also revealed many problems. Therefore, an in-depth study of the regional factors affecting the development of rural e-commerce is helpful to provide a reference for its better development. Based on the analysis of the current situation of rural e-commerce development, this study collects and organizes the indexes of influencing factors of rural e-commerce. The index system of influencing factors of rural e-commerce development is constructed through data collection and so on. After that, this study adopts the regional fuzzy information theory to evaluate the potential of rural e-commerce development, so as to obtain the main influencing factors of rural e-commerce development.